The Position of the Humanities in New “European” Contexts - Žic Fuchs, Milena (Array, 2011)
This presentation discussed the necessity of a balanced relationship between national and EU funding for the Humanities and Social Sciences. This implies resetting research agendas, both at national and EU level, but also focusing on inter/trans/multidisciplinarity research as well as specific monodisciplinary research in the Humanities.